Nadzwyczajne postępowanie administracyjne a postępowanie sądowoadministracyjne - Majczak, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
A great number of legal remedies for the verification of final administrative decisions implies the possibility of factual coincide between available means of legal protection. Therefore, it is necessary to decode significant rules of exclusion of the double-track verification of final administrative decisions. The solution adopted in Article 56 of the Law on Proceedings before Administrative courts is only fragmentary. Hence is causes confusion in the process of interpretation of law. In view of growing doubts whether it is possible to initiate administrative proceedings in one of the procedures of extraordinary verification of administrative decisions when the same instrument is being reviewed by an administrative court, the President of the Supreme Administrative Court made a motion for a panel of 7 judges to adopt an abstract resolution. In the resolution, the Court permitted the relevant extraordinary proceedings to be initiated, but indicated that it was necessary to suspend such proceedings pursuant to Article 97(1)(4) of the Code of Administrative Procedure.
Keywords: procedural bar; stay of proceedings; review of a final administrative decision; judicial verification